Teachers and students of the Edgren School of Music, Seattle, 1908
Professor Adolph Edgren, a prominent local musician and educator, along with his wife, Emma, operated the Edgren School of Music in Seattle. Professor Edgren was chosen as the day's Music Director in Chief for the Alaska-Yukon-Pacific Exposition, on July 31, 1909, Swedish Day. In addition to various musical ensembles performed by the school and the Grand Swedish Jubilee Choir, Professor Edgren composed several pieces for the Exposition, including "Jubel Kantat," "A Hearty Cheer for Arctic Brotherhood," and "Greeting to Alaska Pioneers." This portrait of Professor and Mrs. Edgren and the students of the Edgren School of Music was taken the year prior to AYPE, in 1908, apparently outside the school's location, 1828 9th Avenue, Seattle. Caption on photo: Complimentary to Pupils 1908 of the Edgren School of Music Caption information source: "Alaska-Yukon-Pacific Exposition (1909): Music at the Fair," Peter Blecha, historylink.org Essay8876 1 photographic print mounted on cardboard: b&w; 12 x 14 in.